EVALUASI PENYELENGGARAAN PROGRAM PENDIDIKAN INKLUSIF DI KOTA PALANGKA RAYA 1 - Sartica, Dwi; Ismanto, Bambang (Kelola: Jurnal Manajemen Pendidikan, 2016)
Inclusive education program (PI) is a product of the policies of the regional government held Education Department of Palangkaraya and must be implemented by all schools. The purpose of this study was to gather information for the evaluation of the implementation of programs in SD Negeri 6 Bukit Tunggal, SMP Negeri 3 and SMAN 4. The data was collected throughinterview and documentation study. Evaluation model used in this study is the CIPP. The subjects of this study were principal, regular teachers, and Guidance and Counceling Teachers of each school. The results of the evaluation context showed that the program has met the needs of PIs and parents of students with special needs; the population served were students with special needs and is still in the category of mild to moderate; as well as helpful programs sothat school the full confidence of the public and an opportunity to increase the number of crew members who served. The results of the evaluation input indicated that the special facilities were inadequate; school involving all stakeholders in the school and some from outside; financing comes from use of the funds, scholarships, and / or budget; and the school does not have Special Guidance Teacher (SGT). The results of the evaluation process showed that newEducation Department of Palangkaraya one to monitor and evaluate; teacher competence was good enough; learning in general but the treatment given on an individual basis, and extracurricular activities reserved for the crew; facilities not helpful enough; and the obstacles encountered was no SGT, facilities not adequate, specialized training has not been evenly distributed, no further monitoring of the relevant Department, and there is no standard for theevaluation system. The results of the product evaluation showed that the academic and non academic achievement of were students with special needs good enough. In addition, there were many number of crew members who served. The implication of this study is to provide recommendations for schools and related agencies for the improvement of the sustainability of the program.